Revealing Indonesia's Reluctance to Participate in the Regional Cooperation Agreement on Combating Piracy and Armed Robbery against Ships in Asia (ReCAAP) - Achmad Ismail (Indonesian Journal of Peace and Security Studies (IJPSS), 2021)
The Vision of President Jokowi to create Indonesia as a world maritime axis meets a variety of challenges. Piracy and armed robbery are the real threat faced by each state, in particular, Indonesia as a maritime (archipelagic) state. The escalation more is realized in real life. For facing the challenges, states in Asia create The Regional Cooperation Agreement on Combating Piracy and Armed Robbery against Ships in Asia (ReCAAP). Unfortunately, Indonesia is not joining the regional cooperation that makes this phenomenon is very interesting to investigate. Therefore, this article argues that Indonesia's foreign policy did not ratify ReCAAP's regional cooperation was identified from various factors including systemic sources, societal sources, governmental sources & idiosyncratic sources. This article uses a qualitative research method with a case study approach. Data collection techniques in this article use a literature study where is sourced from several kinds of literature. This article concludes that the four factors above that influenced Indonesian policy did not ratify the ReCAAP regional cooperation.